Energizing Africa Sustainably: Lessons from Ghana’s Electricity Infrastructure - Quartey, Jonathan D. (International Journal of Publication and Social Studies, 2020)
Africa’s electricity infrastructure shortfall presents an opportunity for sustainable infrastructural investment. This paper assessed Africa’s electricity infrastructure for sustainability, through a systems holistic model. To scale down the analytical procedure for specific country application, data was analyzed from Ghana, one of Africa’s best examples of high achievements in access to electricity, tipped for universal access by 2030. The study found that Ghana’s electricity infrastructure does not satisfy the requirements for environmental, economic and social sustainability. Electricity infrastructure in Ghana has been 453% more fossil fuel based than the recommended global requirement. Also, industry electricity tariffs have gone up by at least 276% since 2011, with worsening externality per capita due to investments in unsustainable electricity infrastructure. Thus, electricity infrastructure has worsened livelihoods in Africa, creating a disincentive for investment and failing to deliver sustainable development. African countries must re-examine their electricity infrastructure investments, not only by kilowatt-hours but also based on sustainability indicators, in order not to further aggravate poverty and deprivation on the continent.